Perilaku Penggunaan Portal E-office di Bank XYZ Dengan Pendekatan Model UTAUT - Priyadi, Robi; Daryanto, Arief; Hermadi, Irman (Jurnal Aplikasi Bisnis dan Manajemen, 2017)
Bank XYZ, one of the state-owned banks in Indonesia has been implementing a web-based electronic office system, namely DiO (Digital Office System), since 2014. DiO provides a number of office automate facilities, such as office administration/management, word processing, and communication/mailing system. This research aims to analyze the most affecting factor that underlies the acceptance and usage of DiO by the employees (respondents) using the Unified Theory of Acceptance and Use of Technology (UTAUT) model approach. The study was conducted by using online survey involving employees of Bank XYZ. 380 samples were collected by using the judgment sampling method. Structural Equation Model (SEM) was applied to analyze the data collected from the respondents. The result shows that the employees’ use behavior of DiO was significantly influenced by the behavioral intention to use and facility condition. Furthermore, the employees’ behavioral intention to use DiO system is significantly influenced by performance expectancy; on the contrary, effort expectancy and social influence have no effect.Keywords: e-office, DiO System, UTAUT model, behavioral intention to use, use behavior, SEMABSTRAKBank XYZ, salah satu bank milik pemerintah yang telah menerapkan sistem elektronik office, disebut DiO (Digital Office System) sejak tahun 2014. Aplikasi DiO mengakomodir beberapa fasilitas otomasi dalam bentuk pengelolaan administrasi perkantoran, pengolahan kata dan komunikasi/pengiriman surat menyurat. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang memengaruhi perilaku penggunaan DiO oleh karyawan Bank XYZ dengan pendekatan model the Unified Theory of Acceptance and Use of Technology (UTAUT). Penelitian telah dilaksanakan dengan melibatkan karyawan Bank XYZ sebagai responden. Sampel sebanyak 380 dikumpulkan dengan menggunakan metode judgement sampling. Data dianalisis dengan Structural Equation Model(SEM). Hasil penelitian menunjukkan perilaku penggunaan DiO secara aktual (use behavior) dari karyawan Bank XYZ secara signifikan dipengaruhi oleh behavioral intention to use dan fasilitas pendukung. Behavioral intention to use DiO karyawan Bank XYZ hanya terbentuk karena pengaruh harapan kinerja sementara harapan usaha dan pengaruh sosial tidak berpengaruh.Kata kunci: e-office, sistem DiO, model UTAUT, behavioral intention to use, use behavior, SEM